PENGARUH TRANSAKSI PEMBAYARAN NON-TUNAI TERHADAP PROFITABILITAS PERUSAHAAN RETAIL PT. MATAHARI DEPARTMENT STORE Tbk TAHUN 2015-2019 - Gunawan, Iba; huswatun, ana (Universitas Banten Jaya, 2021)
This study determines how much influence non-cash payment transactions have on Return on Assets. The method uses a quantitative approach. This research was conducted by processing secondary data in the form of financial statements and non-cash payment transaction data of PT. Matahari Department Store Tbk, 2015 - 2019. Both of them were analyzed and calculated statistical tests using SPSS Version 2.0 software. Data analysis uses a simple linear regression test, person correlation test, determinant test, and ttest. The results of the simple linear regression test in the variable considered constant are 14.664. If there is an addition, the effect of profitability will increase by 0.993. The results of testing the Pearson Bivariate correlation coefficient based on the significance value of Sig. (2-tailed): The Sig. (2-tailed) between non-Cash Payment Transactions (X) and Profitability (Y) is 0.000 <0.05, which means that there is a significant correlation between the Non-Cash Payment Transaction Variable and the Profitability Variable. The test results of the coefficient of determination (R2) value R = 0.892 and R2 = 0.795 mean that the regression model obtained able to explain non-cash payment transactions can affect profitability by 79.5% while the remaining 20.5% is influenced by other variables. From the partial test results on the coefficient table, it can be seen that the t-count value of non-cash payment transactions is 3.409 with a value of 3.182 (tcount> ttable = 3.409> 3.182) which means that Ho is rejected and Ha is accepted, so non-cash payment transactions have an effect significant to Return on Asset at PT. Matahari Department Store Tbk. In this case, it shows that non-cash payment transactions are able to increase Return on Assets at PT. Matahari Department Store Tbk.